Educators’ Reflections on Empowerment in a Gender Responsive Program for Women Offenders - Carolyn L. Sandoval; Lisa M. Baumgartner (Adult Education Research Conference, 2017)
We explore women educators’ experiences teaching in a gender-responsive program for women who are incarcerated. Themes including fostering empowerment, motivations for teaching, and tensions teaching emancipatory content in jail.
Keywords: educators; jail; gender-responsive programs; emancipatory learning